Reflecting Images. The Front Page of Icelandic Tourism Brochures - Gunnarsdóttir, Gudrún Thóra (Presses de l'Université du Québec, 2011)
One of the most popular tools to promote tourist destinations is the publication of travel brochures. This study explores image-making in material that promotes Icelandic tourism on a regional and national basis and its effect on the conceptualization of different regional tourist destinations. The pictorial content of the front page of the main travel brochures has been studied in order to identify images put in the foreground by both the national tourism board as well as various regional destinations’ marketing bureaus. In addition, key players in tourism development and regional marketing have been interviewed about the destination image-making process and the interaction between regional and national image-making.